SHOWROOM MOBIL DENGAN PENDEKATAN ARSITEKTUR HIGHTECH DI SURAKARTA - Riyan Pandu Wijayanto; Suparno Suparno; Hari Yuliarso (Universitas Sebelas Maret Surakarta, 2015)
Car Showroom Design of Architectural Approach Hightech in Surakarta triggered by the growth of four-wheeled vehicles is increasing from year to year and the needs of the community will maintenace or care of the car is also increasing. This showroom is made as facilities for various service activities container full four-wheeled vehicles in one building. Hightech architecture is used as a showroom for design approach in line with the image of a car showroom representing a technology, sophisticated, flexible, functional. The method used is a method of designing architecture with Hightech Architecture approach. Architecture Hightech made for functional reasons, but for the future, this architecture could be an attempt to expose and play with building elements both inside and outside elements. By using this approach showroom building is designed with aesthetic appearance and good, as it represents the function of the container activities of the facility four-wheel vehicles in it. Keywords: Architecture, Architecture Hightech, Car Showroom, Car Facilities